Answer:
t3 = 8, t5 = 14
Step-by-step explanation:
t3 = 2 + (3-1) × 3
t3 = 2 + (2) × 3
t3 = 2 + 6
t3 = 8
t5 = 2 + (5-1) × 3
t5 = 2 + (4) × 3
t5 = 2 + 12
t5 = 14
You can do it this think and if you can't I will help you
Y can equal 3, if x=0. i hoped i helped. please mark my responce as brainiest.
Answer:
175pi units^3
Step-by-step explanation:
A P E X- just did it
Answer:
True
Step-by-step explanation:
Evaluate 18 x - 2 (3 x + 1) = 5 x - 16 where x = -2:
-2×18 - 2 (1 - 2×3) = -2×5 - 16
3 (-2) = -6:
-2×18 - 2 (-6 + 1) = -2×5 - 16
1 - 6 = -5:
-2×18 - 2-5 = -2×5 - 16
18 (-2) = -36:
-36 - 2 (-5) = -2×5 - 16
-2 (-5) = 10:
10 - 36 = -2×5 - 16
5 (-2) = -10:
10 - 36 = -10 - 16
10 - 36 = -26:
-26 = -10 - 16
-10 - 16 = -26:
-26 = -26
-26 is equal to -26:
Answer: True